Employee knowledge acquisition as the central mechanism for creativity in an Indonesian petrochemical state-owned enterprise: A PLS-SEM study of transformational leadership, ambidextrous organisational culture, and employee personality - Nursaman, Erdiasa; Rahardjo, Kusdi; Utami, Hamidah Nayati; Afrianty, Tri Wulida (Edelweiss Applied Science and Technology, 2026)
This study examines how transformational leadership (TL), ambidextrous organisational culture (AC), and employee personality (EP) influence employee creativity (EC), positing employee knowledge acquisition (EKA) as a central mediating mechanism within an Indonesian state-owned petrochemical enterprise. A quantitative cross-sectional survey was administered to 238 permanent employees, analysed using PLS-SEM with a two-stage higher-order construct approach in SmartPLS 4 with 5,000-sample bootstrapping. EP is the strongest predictor of EKA (β = 0.666, p < .001) and EC (β = 0.445, p < .001). AC significantly predicts EKA (β = 0.203, p < .05) but not EC directly. TL shows no significant effect on EKA or EC. EKA is the dominant predictor of EC (β = 0.560, f² = 0.808), explaining 88.1% of EC variance. EKA fully mediates the AC–EC relationship and partially mediates EP–EC (VAF = 45.6%). EKA is the critical cognitive conversion mechanism through which organisational context and individual disposition generate creativity. Organisations should prioritise personality-informed recruitment, embedded knowledge infrastructure, and systemic leadership design to maximise creative output in state-owned enterprises.